2020
DOI: 10.1002/aorn.12885
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Analysis of Reusable and Disposable Surgical Gowns

Abstract: Surgical gowns help protect patients from exposure to microorganisms and serve as personal protective equipment for perioperative staff members. Medical textiles, including surgical gowns, are available as reusable and disposable products. Health care facility administrators and leaders who endeavor to use environmentally sustainable practices require current data for decision making. This study analyzed all activities from the extraction of fossil materials from the earth to the end‐of‐life disposal of reusab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 28 publications
0
76
1
4
Order By: Relevance
“… 75 Woven polyester (T280) fabrics provided better water-repellency and increased protection against strike-through liquids and pathogens, but the thermal comfort could be a problem. 151 A recent study of the North America market 152 reported that the majority of modern reusable surgical gowns are composed of woven polyethylene terephthalate (PET) fabric in the noncritical zones and knitted PET fabric in the critical zones. A barrier fabric is used to reinforce the knitted PET in the critical zones, where 70% of the barrier fabric is based on expanded polytetrafluorethylene (PTFE) and the remaining 30% is based on breathable polyurethane (PU) barrier membranes.…”
Section: Personal Protective Textilesmentioning
confidence: 99%
See 2 more Smart Citations
“… 75 Woven polyester (T280) fabrics provided better water-repellency and increased protection against strike-through liquids and pathogens, but the thermal comfort could be a problem. 151 A recent study of the North America market 152 reported that the majority of modern reusable surgical gowns are composed of woven polyethylene terephthalate (PET) fabric in the noncritical zones and knitted PET fabric in the critical zones. A barrier fabric is used to reinforce the knitted PET in the critical zones, where 70% of the barrier fabric is based on expanded polytetrafluorethylene (PTFE) and the remaining 30% is based on breathable polyurethane (PU) barrier membranes.…”
Section: Personal Protective Textilesmentioning
confidence: 99%
“…(g) Comparison of environmental impact of reusable (R) and disposable (D) surgical gowns. 152 NRE = natural resource energy, GWP = global warming potential.…”
Section: Global Market and Supply Chain For Personal Protective Clothmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many institutions still mainly use reusable surgical gowns for their surgeries for various reasons. 3,4 Waterproof or water-resistance material is one of the materials commonly used for reusable surgical gowns. These cloth materials give the gown a smooth surface, which makes them slippery.…”
Section: Introductionmentioning
confidence: 99%
“…Vozzola et al [12] Knit PET/expanded polytetrafluoroethylene reusable surgical gown vs nonwoven PET/polypropylene surgical gown…”
mentioning
confidence: 99%